Mechanisms of Varicella-Zoster Virus Neuropathogenesis in Human Dorsal Root Ganglia - Reichelt, Mike (American Society for Microbiology (ASM), 2008)
Varicella-zoster virus (VZV) is a human alphaherpesvirus that infects sensory ganglia and reactivates from latency to cause herpes zoster. VZV replication was examined in human dorsal root ganglion (DRG) xenografts in mice with severe combined immunodeficiency using multiscale correlative immunofluorescence and electron microscopy. These experiments showed the presence of VZV genomic DNA, viral proteins, and virion production in both neurons and satellite cells within DRG. Furthermore, the multiscale analysis of VZV-host cell interactions revealed virus-induced cell-cell fusion and polykaryon formation between neurons and satellite cells during VZV replication in DRG in vivo. Satellite cell infection and polykaryon formation in neuron-satellite cell complexes provide mechanisms to amplify VZV entry into neuronal cell bodies, which is necessary for VZV transfer to skin in the affected dermatome during herpes zoster. These mechanisms of VZV neuropathogenesis help to account for the often severe neurologic consequences of herpes zoster.